Two pioneers of epigenetics: their different paths to chromatin research and DNA methylation, and general reflections on epigenetics - Deichmann, Ute (Frontiers in Epigenetics and Epigenomics, 2024)
The concept of chromatin as a complex of DNA (nuclein at the time) and proteins in the nucleus of eukaryotic cells was generated in the late 19th century. Since the late 20th century, research on DNA methylation that originated in the 1970s and chromatin research have also been labelled epigenetics, a term that originated in developmental biology in the 1940s. Epigenetics now comprises many different research strands related to the regulation of gene activity, such as chemical modifications of histones and DNA, chromatin organization, genome architecture, different types of RNA molecules, and others. To show the various paths on which epigenetic research has developed, I present research and reflections of two pioneers of what later became called epigenetics, Gary Felsenfeld and Adrian Bird. They began their scientific career in very different scientific contexts with both of them crucially contributing to the development of modern chromatin research and the understanding of DNA methylation, respectively. The article is based on authorized transcripts of interviews that I modifications and other transcription regulators that act in the context of chromatin. Research termed epigenetics remained marginal until the end of the 20th century. It started to rise rapidly when heritability was added to its definition. At the same time, the diversity of researchers' understandings and definitions of epigenetics increased dramatically, extending from molecular research to the studies of chromatin structure and nuclear organization. In molecular biology, cell biology, and chromatin research, epigenetics can relate to research on chromatin structure and function, nucleosome remodeling, causes and functions of DNA and histone modifications, or the study of the self-perpetuation of signals as a requirement for cells to retain memories of past states. "Epigenetics" also refers to long non-coding RNA in transcriptional regulation and small interfering RNA as inhibitors of transcription and translation. Many epigenetic studies look at the interaction of DNA sequence-specific transcription factors, repressors, and RNA polymerases with histone proteins, chromatin compaction, looping, etc. in gene regulation processes.